2006
DOI: 10.1007/s10620-006-3190-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Sildenafil on Small Intestinal Motility and Myoelectrical Activity in Dogs

Abstract: Previous studies have shown that sildenafil inhibits the esophageal motility in both humans and animals. The aim of this study was to investigate the effects of sildenafil on intestinal myoelectrical activity and motility. The study was composed of 2 experiments and performed in 7 healthy female dogs with a duodenal cannula 20 cm beyond pylorus (19-26 kg). The first experiment was designed to study the effects of sildenafil on intestinal myoelectrical activity and it included 2 sessions each consisting of 30-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Sildenafil is absorbed systemically and has well-established relaxation effects on smooth muscle that might affect transit. Several studies have reported a reduction in esophageal contractile force by sildenafil treatment, particularly in patients with dysmotility disorders, but this effect is less pronounced in the normal esophagus and in the lower intestine [38,39,40,41,42]. Reduced muscular contractility cannot explain the results reported here because this would be expected to further increase transit time in our disease models, but as shown here, sildenafil reduced transit time.…”
Section: Discussioncontrasting
confidence: 47%
“…Sildenafil is absorbed systemically and has well-established relaxation effects on smooth muscle that might affect transit. Several studies have reported a reduction in esophageal contractile force by sildenafil treatment, particularly in patients with dysmotility disorders, but this effect is less pronounced in the normal esophagus and in the lower intestine [38,39,40,41,42]. Reduced muscular contractility cannot explain the results reported here because this would be expected to further increase transit time in our disease models, but as shown here, sildenafil reduced transit time.…”
Section: Discussioncontrasting
confidence: 47%
“…The dominant power of the gastric slow wave has been associated with the contractility of the stomach; an increase in the dominant power of the gastric slow wave was reported to be accompanied with an increase in gastric motility and vice versa 29,31 . In a separate study, we investigated the effects of sildenafil on intestinal slow waves 32 and found that sildenafil significantly reduced the amplitude but not the frequency or regularity of the intestinal myoelectrical activity.…”
Section: Discussionmentioning
confidence: 98%